Adolescent mental wellness: a systematic review protocol of instruments measuring general mental health and well-being. Issue 8 (23rd August 2020) - Orth, Zaida; van Wyk, Brian
Abstract : Introduction: The promotion of mental health well-being among global adolescent populations is of great public health and social significance. This is particularly true for adolescents living with chronic illnesses as studies have shown that these populations are at higher risk for developing mental health problems. There is vast recognition of the need for age and culturally appropriate interventions to promote mental well-being and prevent mental health problems. In stark contrast, there is a dearth of relevant measures of mental well-being for adolescents. Our proposed systematic review aims to identify measures of mental well-being and to assess content, psychometric properties and relevance to adolescent populations. Methods and analysis: The systematic review methodology will be guided by the seven steps proposed by Eggar, Davey and Smith. Documents will be sourced from electronic databases (Academic Search Complete, Educational Resource Information Center, Medical Literature Analysis Retrieval System Online, Cumulative Index of Nursing and Allied Health Literature plus, PsyArticles, SocIndex and Sabinet). All documents will be exported to Mendeley and two reviewers will independently screen the titles, abstracts and full texts for inclusion. Any discrepancies will be resolved by a third party. We will include studies published in all languages from 2000 to 2020, that use an instrument(s) that measure mental well-being among adolescent populations. Studies reporting on clinically significant mental illnesses or disorders will be excluded. A descriptive meta-synthesis approach will be used to identify and describe the mental health instruments used among adolescent populations, and to report on the psychometric properties. Ethics and dissemination: Ethical approval is not required. The results of this review will be disseminated through a peer-reviewed publication as well as conference presentations.